Ectopic pregnancy in a case of congenital mullerian anomaly: a diagnostic dilemma - Brahmbhatt, Sanjay; Makhija, Amrita; Brahmbhatt, Jayna; Patel, Yagnesh V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ectopic or extrauterine pregnancy occurring in a case with mullerian defect is very rare and poses diagnostic challenges. Undescended and non-communicating fallopian tubes are extremely rare mullerian anomalies. Here authors present a case of ectopic pregnancy occurring in an undescended non-communicating fallopian tube in a patient with unicornuate uterus with absent horn, which was managed laparoscopically. A 32-year-old lady, diagnosed case of left unicornuate uterus with absent right horn, was referred to us with the suspicion of ruptured ectopic pregnancy. The abdominopelvic ultrasound showed a soft tissue lesion of size 32×24 mm, towards the right lateral pelvic wall near the iliac vessels, with increased vascularity on colour flow doppler. The patient underwent laparoscopy which showed left sided unicornuate uterus with normal left tube and ovary. The right uterine horn was absent. An undescended right ovary and tube were found attached to the peritoneum at the level of pelvic brim along the right lateral pelvic wall. Right sided tubal ectopic pregnancy with rupture was present along with 300-350 cc of hemoperitoneum. The patient was treated with laparoscopic right sided total salpingectomy. In patients with unicornuate uterus and atypical presentation, ectopic pregnancy should be ruled out in an undescended non-communicating fallopian tube. Salpingectomy of incidentally diagnosed non-communicating fallopian tubes is recommended to prevent future ectopic pregnancy.